1992
DOI: 10.2175/wer.64.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Process control factors influencing Nocardia populations in activated sludge

Abstract: Bench‐scale activated sludge experiments were conducted on Sacramento, California, primary effluent to determine the effect of various process control factors on Nocardia populations in activated sludge. It was possible to wash Nocardia out from activated sludge at a sufficiently low MCRT. The washout MCRT for bench‐and full‐scale activated sludge plants was related to the temperature by the Arrhenius equation. Foam trapping was shown to be a major factor in increasing Nocardia populations in activated sludge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 3 publications
1
34
0
Order By: Relevance
“…They also reported that if the MCRT was less than 5 days unstable foam was observed using the aeration foaming potential test. Cha et al (1992) …”
Section: Reduction In Sludge Agementioning
confidence: 99%
“…They also reported that if the MCRT was less than 5 days unstable foam was observed using the aeration foaming potential test. Cha et al (1992) …”
Section: Reduction In Sludge Agementioning
confidence: 99%
“…2). At the same temperature (ϳ24°C) as the one used in this study, Cha et al (10) previously suggested that a 1.6-day MCRT or SRT could wash out nocardioform foaming. However, such a reduction during the winter slow-growth period for heterotrophic bacteria could cause a marked negative effect on floc size, because extracellular polymer formation by bacteria occurs 30 to 40 h after their maximum growth (49), and also settling at the CWRP, as reported previously (42).…”
Section: Discussionmentioning
confidence: 94%
“…3a); however, many reports on nocardioforms in mixed liquors and surface foams of aeration tanks at full-scale plants have associated growth with summer months (14,55). A previous study of bench-scale activated sludge also found higher nocardioform filament counts at warmer temperatures when the MCRT was constant (10). The foaming episode in our study did occur as the temperature increased (late winter), which was agreement with previous studies from the Midwest, where filamentous bacterial growth and foaming occurred during late spring or summer, when temperatures increased 4°C to 6°C (14,48).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For initial growth experiments the medium was either LB [27], or mineral salts medium [5] containing 0.5% (w/v) sodium acetate trihydrate. Single colonies of the untransformed and vgb-bearing G. amarae were inoculated into 5 ml of medium and grown overnight at 30°C and 200 rpm.…”
Section: Growth Measurementsmentioning
confidence: 99%